What has it cost - Cottrell, Mary Emeline (My University, 1891)
Introduction: It is customary for students at the close of their course of study to estimate as nearly as possible the cost of their training. And he is considered careless indeed, who cannot tell where and how his time and money have been spent. But it is not so easy to complete the cost as it seems at first thought, unless the amount of hard cash employed be the only thing considered; board, clothing, books, amusements, medical attendance and the like, are the visible returns for the money spent. But what student would be willing to consider even this important element, the sum total of expenditures. Good hard work and plenty of it is part of the price each student must pay if he would win a desirable place among his fellows. This is worth a great deal without having any cash value. The value of the student’s time is variously estimated. Some people consider that an average farmer’s boy spends twenty dollars worth of time each month while he is pursuing his studies.
Citation: Cottrell, Mary Emeline. What has it cost. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: College; Education; Ttuition; Expenditures; Theses; Manuscripts (documents)